Efficacy of anifrolumab on skin, joint and lung involvement in anti-MDA5 positive dermatomyositis: a case report - Pettorossi, Federico; Brischigliaro, Laura; Bracalenti, Marisol; Di Gregorio, Aurora; Moccaldi, Beatrice; Depascale, Roberto; Zen, Margherita; Zanatta, Elisabetta; Gatto, Mariele; Doria, Andrea; Iaccarino, Luca (Frontiers in Immunology, 2025)
A 55-year-old woman was diagnosed with anti-melanoma differentiation-associated gene 5 (anti-MDA5) positive dermatomyositis (DM) in 2020, having low grade fever, weight loss, arthritis in small joint of hands, erythematous-desquamative lesions on hands, cuticle dystrophy and severe skin ulcerations. Firstly, she was treated with cyclosporine (CsA), soon discontinued due to gastrointestinal intolerance. She was subsequently treated with steroid pulses, hydroxychloroquine (HCQ) and mycophenolate (MMF), without improvement. In March 2021 she started therapy with intravenous immunoglobulins (IVIG) and prostanoids, leading to ulcer improvement, but stopped due to gastrointestinal intolerance. A chest high resolution computed tomography (HRCT) done in June 2021 showed interstitial lung disease (ILD). In September 2021 rituximab (RTX) was stopped at the first infusion due to gastrointestinal intolerance. From January 2022 the patient also started to walk with difficulty due to development of deep asthenia. Therapy with various Jak inhibitors was started (first tofacitinib, then baricitinib, finally upadacitinib), leading to improvement of cutaneous ulcers, but stopped every time after a few months due to gastrointestinal intolerance and dizziness. In August 2023 during hospitalization a spirometry showed reduction of diffusion capacity of the lung for the carbon monoxide (DLCO). In June 2024, in consideration of poor disease control and refractoriness of the disease (loss of appetite and weight, worsening of asthenia which forced the patient into a wheelchair, persistence of polyarthritis, skin ulcers, alopecia, Gottron’s signs, radiological progression of ILD), she was hospitalized again and Anifrolumab (ANI) was started in July 2024 (300 mg IV every four weeks). After four infusions the patient reported improved appetite with significant weight gain, resolution of arthritis and disappearance of cutaneous ulcers, Gottron’s sign and alopecia. In February 2025, after seven ANI infusions, a HRCT demonstrated a significant radiological improvement of the ILD compared to 2024, and spirometry showed significant improvement of DLCO compared to 2023. In this period, no adverse effects were observed from the new therapy. After twelve total infusions, constitutional, articular and cutaneous involvement remained in good control. This case suggests the potential efficacy of ANI in refractory anti-MDA5-positive DM not only on skin manifestation, but also on articular and lung involvement.